Formulating strategy of thé objekt home living facing hypercompetitive environment - Riasmanida Pramestry, Theresa; Toha, Mohamad (The Indonesian Journal of Business Administration, 2016)
Abstract - Creative industries has increased significantly, people nowadays start to appreciate local products that bring up many local designers exist competing each other with their uniqueness and characteristic. Thé Objekt is a retail company that sells home decorative products that focuses offering different products in this dynamic environment. The development of this dynamic market was supported by rapid population growth, the increasing number of creative people who able change taste of style rapidly. Dynamic environment have an important role in product innovation, technological developments and new tastes are created. Therefore, the purpose of this research is to propose how company responds in developing competitive advantage facing hypercompetition environment that occur in this industry. Company finding the answer of these industry wuestions (1) what are Thé Objekt home living’ strategies to win the existing business? (2) What are Thé Objekt home living’s strategies to win and disrupt the future business? (3) What is the ways to fulfill new customer or existing customers better? The steps in solving the above problems include (1) analysis customer's perception of  Thé Objekt’s product or service, (2) data analysis through cluster analysis, (3) analysis of the external environment, (4) analysis of the internal environment, (5) analysis strategy for existing business, (6) analysis hypercompetition strategy, (7) integrate existing strategy and the future, (8) the implementation plan of the strategy. Data, information and knowledge to perform troubleshooting steps are derived from primary data through research and secondary data from existing records.  Keywords: Hyper competition, Home and Living, Business Model Canvas